The impact of severity of antenatal anaemia on maternal and perinatal outcome in Hospital Serdang, Central Malaysia - Tusimin, Maiza; Yazit, Aishah; Zainulddin, Nur Syaza; Vaiappuri, Selvavaani K. N.; Md Noor, Sabariah (OMICS Publishing Group, 2016)
Introduction: Anaemia in pregnancy is one of the most common public health issues in developing countries, affecting approximately 60% of pregnant woman worldwide. Severity of antenatal anaemia had been robustly linked with complications in maternal and perinatal outcome. Objective: This study aimed to analyze the relationship of antenatal anaemia with maternal and perinatal outcome among parturient delivering in Hospital Serdang. Materials and method: This retrospective cross-sectional study was conducted in a tertiary public hospital in Serdang, Selangor. 473 anaemic mothers were recruited from the electronic medical database by clinical notes and cross-referencing to the datasets of relevant test. All subjects received antenatal oral iron supplementation. Results: Multiparous mother contributed to majority of the anemia cases in pregnancy (60.5%). Out of 473anaemic mother suffering from Iron Deficiency Anemia (IDA), 61.3% (n=290) mothers had mild anaemia, 38.5%(n=182), and 0.2% (n=1) mothers had moderate and severe anaemia respectively. A significant association was demonstrated between severity of anaemia with post-partum haemorrhage and small for gestational age. On contrary, severity of maternal anaemia was non-significantly associated with placenta abnormalities, pre-eclampsia and sepsis. Conclusion: Anaemia amongst pregnant women especially multipara imposed a spectrum of health problems to both, mother and child. Prevention is not insurmountable; hence active intervention by all level of health care provider is imperative in order to decrease poor maternal and perinatal outcome.